Indonesian Airlines’ Electronic Ticketing Web Page: Influence of Web Page Dimensions on Customer Satisfaction Leading To Favorable Repeat Purchase Intention - Susanto, Edy (2011)
Electronic commerce (e-commerce) has been widely adopted by companies in different industry to promote and to sell their products and services, including the airline industry. Numerous Indonesian airline companies have employed electronic ticketing (e-ticketing) website service to promote and to sell their air tickets to customers worldwide. It is important to identify if the company’s website has a competitive advantage that could influence customer’s intention of purchasing air ticket electronically. This research is carried out to identify the dimensions of Indonesian airlines’ electronic ticketing web page that influence customer satisfaction. Six (6) dimensions of electronic ticketing web page are examined in this study, including “website design”, “quality information”, “consistent and accurately delivery of promises”, “promptness in response”, “trustworthiness” and “personalization or individualization”. Questionnaire survey is employed to collect the data. The sample size was 350. Data was collected at Jakarta International Airport in Indonesia. Numerous statistical methods were employed to analyze the data collected. Findings showed that “prompt in response”, “trustworthiness”, “website design”, “quality information”, “personalization or individualization”, “consistent and accurate delivery of promise” are in the order of importance that influence customer satisfaction. Recommendations to Indonesian airline companies and future studies are also provided. The outcome of this finding provides a valuable insight to the direct impact of the six (6) dimensions that influence customer satisfaction which lead to favorable purchase intention of air tickets from Indonesian airline’ electronic ticketing web page.